Netralisasi Kebijakan dan Kendala Pasar: Analisis Ekonomi Politik tentang Mengapa Liberalisasi Gagal Mendukung Perguruan Tinggi Swasta di Indonesia - Rizki Hegia Sampurna; Sulaeman Sulaeman; Zahra Laisha Anwar (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study provides a political economy analysis of how higher education liberalisation fails private universities in Indonesia through policy neutralisation and market constraints. Using path analysis, we conducted a census of 20 private universities in Sukabumi, with 60 respondents, to investigate the direct and mediated effects of liberalisation policies on economic performance through student enrolment. Our findings reveal that liberalisation policies have no significant effects on either economic performance or student enrollment, accounting for only 6.7% of enrollment variance. In contrast, student enrollment shows a robust positive relationship with economic performance, accounting for over 50% of institutional performance variance. These results demonstrate how market constraints—demographic limitations, competitive saturation, and resource scarcity—systematically neutralise the benefits of liberalisation for private universities. The absence of liberalisation effects contradicts neoliberal theoretical expectations, while the strong enrollment-performance linkage confirms resource dependence in tuition-dependent models. Our political economy analysis reveals that state policy advantages for public universities create asymmetric competition that undermines private institutions. The study demonstrates how market constraints generate policy-neutralisation effects, necessitating direct enrolment support mechanisms rather than market-oriented reforms for sustainable private university development in constrained contexts.